Once we were bacteria... mitochondria to infinity and beyond - Flaminia Bardanzellu; Maria Cristina Pintus; Vassilios Fanos; Maria Antonietta Marcialis (Hygeia Press di Corridori Marinella, 2018)
Mitochondria, cytoplasmic organelles originated from endosymbiotic bacteria, can be metaphorically described using "Janus bifrons" image, due to their involvement in life, providing cellular energy and resulting essential even for stem cells, but playing a key role also in cell death. Mitochondria own a maternally inherited genome and are the site of aerobic respiration; they can produce proteins, nucleotides, lipids, steroids and heme and result involved in iron homeostasis. Moreover, mitochondria can generate free radicals, break down waste products and represent the primary source of cellular heat. The size and shape of mitochondria depend on the intracellular metabolic status, from tubular presentation to a blob form in case of irreversible damage. Each mitochondrion carries different sets of DNA; when one set accumulates mutations, it can be replaced by another. It has been widely demonstrated that mitochondrial disorders are involved in many pathologies, including autism, multiple endocrinopathies, diabetes, Alzheimer's disease, ataxia, Barth's syndrome, myopathy, and even aging and cancer. Human population is characterized by different mitochondrial DNA haplogroups reflecting the mutations accumulated and useful to characterize genetic diversity. The mitochondrial role also results relevant in pregnancy, providing information about maternal-fetal dyad in physiological and in pathological conditions. Recent evidence suggests that an intriguing bidirectional inter-talk exists between microbiota and mitochondria, influencing cellular homeostasis and metabolism. A recently demonstrated mitochondrial property is the possibility to be transferred from a donor cell to a recipient cell, through a system of tunneling nanotubes. Recently, a promising integrated approach involving omics sophisticate technologies has been applied in mitochondrial pathophysiology. This is still at an early stage, and further studies will clarify such complex genotype-phenotype relationships. In conclusion, mitochondria are not simple energetic organelles but represent dynamic structures communicating with the cell nucleus and even with other cells, influencing metabolism and their targets' functions. More detailed knowledge of their involvement in disease, even though a combined omics approach, could represent a chance for new therapies.